Negative Partiality - Brandt, Josh (Journal of moral philosophy, 2020)
At the outset of the Republic, Polemarchus advances the bold thesis that “justice is the art which gives benefit to friends and injury to enemies”. He quickly rejects the hypothesis, and what follows is a long tradition of neglecting the ethics of enmity. The parallel issue of how friendship (and other positive relationships) affects the moral sphere has, by contrast, been greatly illuminated by discussions both ancient and contemporary. This article connects this existing work to the less explored topic of the normative significance of our negative relationships. I explain how negative partiality should be conceptualized through reference to the positive analogue, and argue that at least some forms of negative partiality are justified. I further explore the connection between positive and negative relationships by showing how both are justified by ongoing histories of encounter (though of different kinds). However, I also argue that these relationships are in some important ways asymmetrical (i.e. friendship is not the mirror image of enmity).